2023
DOI: 10.3390/su151914050
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Demographic and Personal Variables on Post-Retirement Migration Intention of Rural Residents: Evidence from Inner Mongolia, China

Xueqiong Zhou,
Wenhao Feng

Abstract: With the intensification of population aging in rural areas, it becomes increasingly important to analyze the post-retirement migration intention of rural residents and the variables influencing these intentions. However, there is a lack of research on this point. In this study, we focused on rural residents aged 45 to 60 and used the logistic regression model to investigate the demographic and personal variables influencing their post-retirement migration intention. The data used in this study were collected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The 2015 National 1% Population Sampling Survey found that from 1982 to 2015, China's rural population over 60 years old increased by 2.37 times [24]. According to the China Population and Employment Statistical Yearbook, during the period of 2000-2020, the proportion of the rural population aged 65 years and above in China has more than doubled from 7.50% in 2000 to 17.72% in 2020, which is more than double the proportion of the rural population aged 65 years and above, and according to the international standard of aging, China's rural areas have already entered the stage of deep aging [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 National 1% Population Sampling Survey found that from 1982 to 2015, China's rural population over 60 years old increased by 2.37 times [24]. According to the China Population and Employment Statistical Yearbook, during the period of 2000-2020, the proportion of the rural population aged 65 years and above in China has more than doubled from 7.50% in 2000 to 17.72% in 2020, which is more than double the proportion of the rural population aged 65 years and above, and according to the international standard of aging, China's rural areas have already entered the stage of deep aging [25,26].…”
Section: Introductionmentioning
confidence: 99%